2003
DOI: 10.1128/iai.71.5.2318-2325.2003
|View full text |Cite
|
Sign up to set email alerts
|

Trojan Horse Effect: Phagocyte-Mediated Streptococcus iniae Infection of Fish

Abstract: The salmonid macrophage-like cell line RTS-11 and purified trout pronephros phagocytes were used to analyze in vitro entry and survival of two Streptococcus iniae serotypes. Efficient invasion by S. iniae occurred in both cells, but only the type II strain persisted in pronephros phagocytes for at least 48 h. Ex vivo models of opsonin-dependent phagocytosis by pronephros phagocytes demonstrated increased phagocytosis efficacy. Analysis of phagocytes collected from diseased fish demonstrated that ϳ70% of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 51 publications
2
66
0
Order By: Relevance
“…Another possibility is that the bacteria simply use the phagosome as a safe haven where they are protected from host immune responses and exposure to antimicrobials without replicating. Zlotkin et al (2003) reported a similar phenomenon in salmonid phagocytes exposed to S. iniae. Dubbed the 'Trojan horse effect', these investigators demonstrated that phagocytized S. iniae not only survive in fish macrophages, but induce apoptosis of these cells, effectively minimizing the host immune response while being transported and delivered to typically inaccessible regions such as the central nervous system.…”
Section: Discussionmentioning
confidence: 57%
“…Another possibility is that the bacteria simply use the phagosome as a safe haven where they are protected from host immune responses and exposure to antimicrobials without replicating. Zlotkin et al (2003) reported a similar phenomenon in salmonid phagocytes exposed to S. iniae. Dubbed the 'Trojan horse effect', these investigators demonstrated that phagocytized S. iniae not only survive in fish macrophages, but induce apoptosis of these cells, effectively minimizing the host immune response while being transported and delivered to typically inaccessible regions such as the central nervous system.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, zfIFN1 is able to rapidly induce the expression of NOS2b, which might contribute to the killing of S. iniae by macrophages by means of the production of reactive nitrogen and oxygen intermediates. The involvement of fish macrophages in the elimination of S. iniae is thought to be essential because the capsule of this bacterium impairs phagocytic clearance and contributes to virulence (22), and the bacterium is able to multiply within macrophages and has the ability to kill macrophages via the induction of apoptotic processes (19).…”
Section: Discussionmentioning
confidence: 99%
“…The virus stock was propagated in EPC cells and titrated in 96-well plates according to Reed and Muench (18). The strain KFP 404 (serotype II) of Streptococcus iniae was provided by Dr. A. Eldar (The Hebrew University-Hadassah Medical School, Jerusalem, Israel) and cultured in brain/heart infusion broth as described previously (19). Ten adult zebrafish were challenged at 26°C in 10-liter tanks i.p.…”
Section: Infection Assaysmentioning
confidence: 99%
“…The virus stock was propagated in EPC cells and titrated in 96-well plates according to the report of Reed and Muench (32). The strain KFP 404 (serotype II) of S. iniae was kindly provided by Dr. A. Eldar and cultured in brain-heart infusion broth as described previously (33). Ten adult zebrafish were challenged at 26°C in 10-liter tanks by i.p.…”
Section: Infection Assaysmentioning
confidence: 99%